Advances of Regulatory B Cells in Autoimmune Diseases - Zhu, Qiugang; Rui, Ke; Wang, Shengjun; Tian, Jie (Frontiers in Immunology, 2021)
With the ability to induce T cell activation and elicit humoral responses, B cells are generally considered as effectors of the immune system. However, the emergence of regulatory B cells (Bregs) has given new insight into the role of B cells in immune responses. Bregs exhibit immunosuppressive functions via diverse regulatory mechanisms, including the secretion of anti-inflammatory cytokines and direct cell contact. The balance between Bregs and effector B cells is of vital importance to immune tolerance. In this review, we focus on recent advances in our understanding of Bregs and their functional role in autoimmunity.